Classification of cat ganglion retinal cells and implications for shape-function relationship - Coelho, Regina Celia [UNESP]; Valenti, Cesare; Tanaka, Julia Sawaki [UNESP]; Da Fontoura Costa, Luciano (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This article presents a quantitative approach to ganglion cell classification by considering combinations of several geometrical features including fractal dimension, symmetry, diameter, eccentricity and convex hull. Special attention is given to moment and symmetry-based features. Several combinations of such features are fed to two clustering methods (Ward's hierarchical scheme and K-Means) and the respectively obtained classifications are compared. The results indicate the superiority of some features, also suggesting possible biological implications. © 2001 IEEE.